Penentuan Konsentrasi Radionuklida Alam Di Kawasan Terdampak Banjir Lahar Dingin Gunung Marapi Sumatera Barat - Novi Afriani; Ramacos Fardela; Dadong Iskandar; Kusdiana; Wahyudi (Jurnal Fisika Unand, 2026)
Research has been carried out to determine the activity concentrations of radionuclides Ra-226 (Radium-226), Th-232 (Thorium-232), and K-40 (Potassium-40) in the Bukik Batabuah area, West Sumatra. The main objective of this research was to compare radionuclide levels in soils affected by cold lava floods with those exposed only to volcanic ash, and to assess whether the cold lava flow contributed to increased radionuclide concentrations. Measurements were performed using an HPGe (High Purity Germanium) gamma spectrometer. Soil samples were collected from six locations impacted by the cold lava flow and from three locations affected by ash from the Mount Marapi eruption. The results indicated that Ra-226, Th-232, and K-40 were detected in all samples. The average activity concentrations in soil affected by the cold lava flow were 14.92 ± 0.62 Bq/kg for Ra-226, 18.37 ± 0.83 Bq/kg for Th-232, and 342.15 ± 7.85 Bq/kg for K-40. In contrast, soils not affected by the cold lava flow showed average values of 10.99 ± 0.62 Bq/kg for Ra-226, 22.34 ± 1.03 Bq/kg for Th232, and 191.68 ± 5.06 Bq/kg for K-40. A t-test statistical analysis indicated significant differences between the two groups of samples. Based on PERKA BAPETEN No. 9 of 2009, the measured activity concentrations in soils around the foothills of Mount Marapi remain below the regulatory limits established by BAPETEN.